Amorphous foil strip brazing filler metal for brazing titanium and high-nitrogen steel as well as preparation method and application of amorphous foil strip brazing filler metal

By using amorphous foil strip brazing material composed of FexTi (100-x) alloy, Zr and Fe, the problem of welding difficulties between titanium and high-nitrogen steel is solved, and the formation of high-quality and high-reliability joints is achieved, which is suitable for Anti-elastic armor protective material.

CN119387957APending Publication Date: 2025-02-07LONGMEN LAB +3
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411565477.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The differences in chemical and physical properties between titanium and high nitrogen steels lead to difficulties in welding. The main problems include residual stress caused by differences in thermal expansion coefficients, the formation of brittle hard intermetallic compounds caused by poor mutual solubility, and the air-squeezing defects caused by nitrogen precipitation.

Method used

Amorphous foil tape brazing material for brazing of titanium and high nitrogen steel is used. The solder material consists of FexTi (100-x) alloy, Zr and Fe, and is prepared by vacuum smelting and single-roll belt swing method to form a uniform chemistry. Components, good wettability and high toughness amorphous structure.

Benefits of technology

This solder can significantly reduce the melting point of the solder, improve the interface strength, reduce nitrogen loss, and avoid the occurrence of air clamp defects, thereby providing high-quality and high-reliability joints, suitable for titanium/high-nitrogen steel in elastic-resistant armor protection materials. Structural parts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119387957A_ABST
    Figure CN119387957A_ABST
Patent Text Reader

Abstract

The invention relates to the field of amorphous brazing filler metal and brazing, in particular to amorphous foil strip brazing filler metal for titanium and high-nitrogen steel brazing and a preparation method and application of the amorphous foil strip brazing filler metal. The amorphous foil strip brazing filler metal for brazing the titanium and the high-nitrogen steel comprises the following components in parts by weight: 35 to 65 parts of FexTi (100-x) alloy, 30 to 50 parts of Zr and 5 to 10 parts of Fe, wherein the value of x ranges from 10 to 50. The amorphous foil strip brazing filler metal for titanium and high-nitrogen steel brazing is uniform in chemical component, good in wettability, good in toughness, bright and neat in surface, excellent in performance when being used for a brazing joint of titanium and high-nitrogen steel, and not prone to cracking.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of amorphous solder and brazing, and in particular to an amorphous foil solder for brazing titanium and high nitrogen steel, and a preparation method and application thereof. Background Art

[0002] High nitrogen steel is a new type of stainless steel that is currently booming. With its high strength, high toughness, high creep resistance and good corrosion resistance, it has become one of the most commonly used structural steels in the manufacture of equipment such as aerospace, ships and weapons. High nitrogen steel itself consumes more plastic deformation energy by increasing the plastic area, which makes it have excellent dynamic impact hardening performance and has broad application prospects in the field of bulletproof armor protection, but its weight is not conducive to the lightweighting of combat vehicles. Titanium, as a rare metal, has become an indispensable and important material in the fields of aerospace and weapons due to its low density, high specific strength and strong corrosion resistance. Titanium and titanium alloys have high structural bearing capacity and good anti-ballistic performance. In terms of performance, they are the best armor protection materials. However, compared with steel, the high cost of titanium and titanium alloys is the biggest obstacle to their widespread application. With the increasing severity of anti-armor threats, the protective armor of combat vehicles is becoming more and more numerous and thicker. Such development in the future will inevitably seriously affect their transportation capacity, the crossing ability of light bridges and mobility. Reliably connecting titanium and high nitrogen steel as a composite structure not only solves the lightweight weapons required for future high-tech local wars, but also solves the cost problem of the large-scale application of titanium and titanium alloys in army equipment. In order to further realize the modernization of weapons and equipment, it is developing in the direction of greater power, lighter weight, higher reliability and longer life.

[0003] However, there are huge differences in chemical and physical properties between titanium and high nitrogen steel, making welding the two extremely difficult. The main problems are: 1. Titanium and high nitrogen steel are metal heterogeneous connections, and the difference in thermal expansion coefficients is too large. The brazed joint will produce large residual stress and cause cracking; 2. High nitrogen steel and titanium have poor mutual solubility, and brittle and hard intermetallic compounds are easily generated during the welding process, weakening the interface bonding strength; 3. The precipitation of nitrogen in high nitrogen steel causes defects such as air inclusion and the formation of brittle and hard phases, reducing the quality of the joint. Therefore, titanium / high nitrogen steel welding is one of the most difficult problems in the field of heterogeneous metal connection.

[0004] Laser arc hybrid welding can reduce the nitrogen escape that occurs during the welding process of high nitrogen steel to a certain extent, thereby avoiding the problem of gas inclusion and nitride precipitation to form a brittle hard phase. For example, "High nitrogen steel laser-arc two-heat source weak coupling welding method" (application number 202010341232.9) proposes a method of changing the flow velocity and direction of the molten pool and reducing the peak temperature of the molten pool to reduce the nitrogen precipitation of the parent material, thereby improving the comprehensive mechanical properties of the joint. However, this method is inconvenient to operate and has low efficiency. It is necessary to regulate the welding process to weaken the coupling effect between the laser and the arc. "A flux-cored welding wire for laser arc hybrid welding of high nitrogen steel" (application number 202211222096.7) provides a method in which aluminothermic reaction occurs under the action of an arc, releasing a large amount of heat to increase the wire feeding speed and thus significantly improve the welding production efficiency. However, although this method can improve the welding production efficiency, it has high requirements for equipment and protective atmosphere in actual production, and the problems of high energy consumption and high cost still exist.

[0005] Vacuum brazing is a method of uniformly heating the parts to be welded by thermal radiation and completing the welding in an oxygen-free and impurity-free vacuum environment. This welding method is widely used in fields that require high-strength and high-purity connections, such as aerospace, weapons and equipment, etc. The vacuum environment can prevent the titanium metal from absorbing hydrogen, oxygen and nitrogen at high temperatures, thereby avoiding the occurrence of defects such as embrittlement, pores, and inclusions in the welding area due to the absorption of a large amount of gas. However, there is currently no information on brazing filler metals for titanium / high nitrogen steel brazing in China, and amorphous foil brazing filler metals have the advantages of low melting point, good fluidity, uniform spreading, good wettability, uniform chemical composition, and excellent brazing joint performance, and are suitable for vacuum brazing. Therefore, it is urgent to develop an amorphous brazing filler metal for titanium / high nitrogen steel brazing to solve the above-mentioned heterogeneous metal connection problem.

[0006] In view of this, the present invention is proposed. Summary of the invention

[0007] The purpose of the present invention is to provide an amorphous foil brazing filler metal for brazing titanium and high nitrogen steel, and a preparation method and application thereof. The brazing filler metal is a titanium-based amorphous foil brazing filler metal, has uniform chemical composition, good wettability, good toughness, a bright and neat surface, and has excellent performance in brazing joints of titanium and high nitrogen steel.

[0008] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0009] One aspect of the present invention relates to an amorphous foil brazing material for brazing titanium and high nitrogen steel, which comprises the following components in parts by weight:

[0010] Fe x Ti (100-x) Alloy 35-65 parts, Zr 30-50 parts and Fe 5-10 parts;

[0011] Among them, the value of x is 10~50.

[0012] The amorphous foil brazing filler metal for brazing titanium and high nitrogen steel has uniform chemical composition, good wettability, good toughness, bright and neat surface, and is used for brazing joints of titanium and high nitrogen steel with excellent performance and not easy to crack.

[0013] Another aspect of the present invention also relates to a method for preparing the amorphous foil brazing material for brazing titanium and high nitrogen steel, comprising the following steps:

[0014] (a) vacuum melting the raw materials under an inert atmosphere to obtain an alloy ingot;

[0015] (b) The alloy ingot is subjected to amorphous forming treatment by a single-roll strip spinning method.

[0016] The method for preparing the amorphous foil brazing material for brazing titanium and high nitrogen steel has a simple and reliable process and is easy to operate in mass production.

[0017] Another aspect of the present invention also relates to the use of the amorphous foil brazing filler metal for brazing titanium and high nitrogen steel or the amorphous foil brazing filler metal prepared by the preparation method of the amorphous foil brazing filler metal for brazing titanium and high nitrogen steel in brazing titanium and high nitrogen steel.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] (1) The amorphous foil brazing material for titanium and high nitrogen steel brazing provided by the present invention is added with Fe x Ti (100-x) The alloy is different from the previous Ti-based brazing filler metal directly adding single-element components. The alloy can fix the N element in the high-nitrogen steel, refine the grains of the phase structure, and improve the interface strength. The addition of the alloy reduces the loss of nitrogen in the high-nitrogen steel brazing process, thereby avoiding the occurrence of a large number of air inclusion defects, and provides high-quality and high-reliability joints for titanium / high-nitrogen steel brazing in bullet-proof armor protection materials. The alloy can significantly reduce the melting point of the brazing filler metal, and the Fe content is relatively low, which can easily diffuse into the Ti lattice, causing the hexagonal close-packed Ti lattice to break to form a disordered structure, thereby improving the amorphous forming ability.

[0020] (2) The amorphous foil brazing material for brazing titanium and high nitrogen steel provided by the present invention is added with Zr. The addition of Zr atoms can infinitely dissolve with Ti and form a continuous solid solution with α-Ti and β-Ti, which has a solid solution strengthening effect on Ti, among which the high-temperature strengthening effect is particularly obvious, and it will not form a brittle intermetallic compound with Ti; in addition, the atomic size ratio of Zr to Fe is greater than 1.2 and the two have a negative mixing enthalpy, which helps to form a random stacking structure with high density and low atomic diffusion rate; the higher the stacking density, the higher the thermal stability of the supercooled liquid and the stronger the ability to resist crystalline phase transformation.

[0021] (3) The amorphous foil brazing material for brazing titanium and high nitrogen steel provided by the present invention has Fe added thereto. The addition of Fe atoms can form a deep eutectic alloy with Ti, thereby improving the alloy properties and preventing or generating a relatively small amount of TiFe and TiFe2 brittle intermetallic compounds in the brazing seam structure, thereby improving the shear strength of the joint.

[0022] (4) The preparation method of amorphous foil brazing material for titanium and high nitrogen steel brazing provided by the present invention is simple and reliable, easy to mass-produce, and Fe x Ti (100-x) The alloy ball milling process reduces the melting point of the brazing filler metal, overcomes the defect of too high melting point of titanium-based brazing filler metal, and makes the brazing process easier to control. By optimizing the brazing process, the amount of brittle intermetallic compound phase and its distribution in the joint can be controlled. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0024] Figure 1 This is a macroscopic picture of the solder of Example 1;

[0025] Figure 2 This is the DSC test curve of the solder of Example 1;

[0026] Figure 3 This is the macroscopic morphology of the titanium / high nitrogen steel brazed joint of Example 1;

[0027] Figure 4 This is the EDS surface scan result of the solder of Example 1;

[0028] Figure 5 This is a microstructural morphology of a titanium / high nitrogen steel joint brazed with the brazing filler metal of Example 1;

[0029] Figure 6 This is the fracture morphology of the titanium matrix of the titanium / high nitrogen steel joint brazed with the brazing filler metal of Example 1. DETAILED DESCRIPTION

[0030] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0031] The present invention selects various constituent elements of an amorphous solder, calculates alloy composition with the aid of a mixed entropy formula that affects a driving force for crystallization, adopts a ball milling method to prepare a binary alloy, and finally draws on a single-roller belt spinning method preparation process to prepare a solder with an amorphous structure, thereby ensuring that the solder has a microstructure dominated by a solid solution, and at the same time controlling the reaction process between the solder and the base material, thereby reducing the formation of brittle compounds during welding.

[0032] One aspect of the present invention relates to an amorphous foil brazing material for brazing titanium and high nitrogen steel, which comprises the following components in parts by weight:

[0033] Fe x Ti (100-x) Alloy 35-65 parts, Zr 30-50 parts and Fe 5-10 parts;

[0034] Here, the value of x is 10 to 50 (for example, 10, 15, 20, 25, 30, 35, 40, 45 or 50).

[0035] In some specific embodiments, Fe x Ti (100-x) The alloy may be, for example, but not limited to, 35, 38, 40, 43, 45, 48, 50, 53, 55, 58, 60, 63 or 65 parts.

[0036] In some specific embodiments, based on weight parts, Zr can be, for example, but not limited to, 30 parts, 33 parts, 35 parts, 38 parts, 40 parts, 43 parts, 45 parts, 48 ​​parts or 50 parts.

[0037] In some specific embodiments, the amount of Fe may be, for example, but not limited to, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts or 10 parts by weight.

[0038] Unlike traditional stainless steel, high nitrogen steel itself has excellent dynamic impact hardening performance, which makes it have great potential in the field of bulletproof armor protection, but its weight is not conducive to lightweight combat vehicles. Titanium and titanium alloys have high structural bearing capacity and good anti-ballistic performance. In terms of performance, they are the best armor protection materials. However, compared with high nitrogen steel, the high cost of titanium and titanium alloys is a huge obstacle to their widespread application. The amorphous foil brazing material provided by the present invention can reliably connect high nitrogen steel and titanium and titanium alloys, which not only solves the lightweight weapons required by future high-tech local wars, but also solves the cost problem of titanium and titanium alloys in large-scale application of army equipment.

[0039] The alloy component Fe in the titanium-based amorphous foil solder of the present invention x Ti (100-x) The addition of alloy is different from the previous Ti-based solder which directly adds single components. x Ti (100-x) The alloy can fix the N element in high nitrogen steel, refine the grains of the phase structure, and improve the interface strength. The high strength, high toughness, non-magnetic, corrosion resistance, and wear resistance of high nitrogen steel are all attributed to the presence of solid solution nitrogen in the parent material. Therefore, the mechanical properties and corrosion resistance of high nitrogen steel joints are closely related to the loss of N elements. x Ti (100-x) The addition of alloy overcomes the loss of nitrogen during high nitrogen steel brazing, thereby avoiding the occurrence of large amounts of gas inclusion defects and providing high-quality, high-reliability joints for titanium / high nitrogen steel brazing in bulletproof armor protection materials. x Ti (100-x) The alloy is made by ball milling, which can significantly reduce the melting point of the solder. The Fe content is relatively low, which can easily diffuse into the Ti lattice, causing the hexagonal close-packed Ti lattice to break and form a disordered structure, thus improving the amorphous forming ability.

[0040] The addition of Zr atoms, a single component in the titanium-based amorphous foil solder of the present invention, can be infinitely solid-dissolved with Ti, can form a continuous solid solution with α-Ti and β-Ti, and has a solid solution strengthening effect on Ti, wherein the high-temperature strengthening effect is particularly obvious, and will not form a brittle intermetallic compound with Ti. In addition, the atomic size ratio of Zr to Fe is greater than 1.2 and the two have a negative mixing enthalpy, which is conducive to forming a random stacking structure with high density and low atomic diffusion rate. The higher the stacking density, the higher the thermal stability of the supercooled liquid, and the stronger the ability to resist crystalline phase transformation.

[0041] The addition of Fe atoms, a single component, in the titanium-based amorphous foil brazing filler metal of the present invention can form a deep eutectic alloy with Ti, thereby improving the alloy performance. It can be seen from the FeTi binary alloy phase diagram that titanium and iron form a eutectic at 1085°C. When the contact is good during brazing and a certain graphite plate pressure is applied, the temperature is heated to a temperature higher than the eutectic temperature, and a eutectic is formed at the interface by mutual diffusion of titanium and iron, thereby connecting titanium and steel to obtain a high-strength joint with good corrosion resistance. Different from the previous titanium-based brazing filler metal brazing of high nitrogen steel, which results in the generation of more TiFe and TiFe2 brittle intermetallic compounds in the brazing seam structure, the shear strength of the joint is greatly improved.

[0042] The main use of this titanium-based amorphous foil brazing material is the vacuum brazing of titanium / high nitrogen steel structural parts in bullet-proof armor protection materials, which can achieve design requirements such as weapon modernization, lightweight, high reliability, and delayed service life.

[0043] The Fe x Ti 100-x Alloy, according to the mixing entropy ΔH and mixing entropy ΔS of FeTi alloy mix , combined with the liquid-solid Gibbs free energy difference ΔG that reflects the driving force of the crystallization process, the range of x is selected to be 10~50.

[0044] The specific formula is as follows:

[0045] ΔG=ΔH-TΔS

[0046] Among them, ΔG is the liquid-solid Gibbs free energy difference, which reflects the driving force of the crystallization process, and ΔH and ΔS are the mixing enthalpy and mixing entropy, respectively.

[0047]

[0048] Where R is the gas constant, C i is the molar content of the component.

[0049] According to the empirical formula:

[0050] ΔG≈ΔS mix ×ΔT

[0051] Here, ΔT is the degree of supercooling, from which we can conclude that a low ΔS corresponds to a low ΔG, that is, a low driving force for the crystallization process, which is not conducive to crystallization.

[0052] Furthermore, the amorphous foil brazing material for brazing titanium and high nitrogen steel comprises the following components in parts by weight:

[0053] Fe x Ti (100-x) Alloy 43.5-61.2 parts, Zr 31.2-47.2 parts and Fe 7.6-9.3 parts;

[0054] Among them, the value of x is 10~50.

[0055] Furthermore, the width of the amorphous foil brazing material for brazing titanium and high nitrogen steel is 3 to 6 mm.

[0056] In some specific embodiments, the width of the amorphous foil brazing material for brazing titanium and high nitrogen steel may be, for example, but not limited to, 3 mm, 4 mm, 5 mm or 6 mm.

[0057] Furthermore, the thickness of the amorphous foil brazing material for brazing titanium and high nitrogen steel is 35-45 μm.

[0058] In some specific embodiments, the thickness of the amorphous foil brazing material for brazing titanium and high nitrogen steel may be, for example, but not limited to, 35 μm, 37 μm, 39 μm, 41 μm, 43 μm or 45 μm.

[0059] Furthermore, the melting point of the amorphous foil brazing material for brazing titanium and high nitrogen steel is 930-1030°C.

[0060] In some specific embodiments, the melting point of the amorphous foil brazing material for brazing titanium and high nitrogen steel may be, for example, but not limited to, 930°C, 940°C, 950°C, 960°C, 970°C, 980°C, 990°C, 1000°C, 1010°C, 1020°C or 1030°C.

[0061] The amorphous foil brazing filler metal for brazing titanium and high nitrogen steel is suitable for all high nitrogen steels.

[0062] Another aspect of the present invention relates to a method for preparing the amorphous foil brazing material for brazing titanium and high nitrogen steel, comprising the following steps:

[0063] (a) vacuum melting the raw materials under an inert atmosphere (with a purity higher than 99.99%) to obtain an alloy ingot;

[0064] (b) The alloy ingot is subjected to amorphous forming treatment by a single-roll strip spinning method.

[0065] The present invention is different from the conventional titanium-based brazing filler metal. x Ti (100-x) The alloy ball milling process reduces the melting point of the brazing filler metal, overcomes the defect of too high melting point of titanium-based brazing filler metal, and makes the brazing process easier to control. By optimizing the brazing process, the amount of brittle intermetallic compound phase and its distribution in the joint can be controlled.

[0066] The amorphous foil solder provided by the present invention does not contain precious metals such as Au and Ag, and does not contain heavy metals such as Ni and Cu, has good economic and practical value, has a simple preparation process, is green and environmentally friendly, and can effectively reduce harm to human body during industrial production and preparation processes.

[0067] Furthermore, the Fe x Ti (100-x) The preparation method of the alloy includes:

[0068] The iron element and the titanium element are mixed, ball-milled and vacuum-dried.

[0069] Furthermore, the ball-to-material ratio of the ball mill is 35-45:1.

[0070] In some specific embodiments, the ball-to-material ratio of the ball milling can be, for example, but not limited to, 35:1, 37:1, 39:1, 41:1, 43:1 or 45:1.

[0071] Furthermore, the ball milling is carried out under the protection of an inert atmosphere (with a purity higher than 99.99%), the inert atmosphere is charged at a pressure of 0.6-0.8 MPa (e.g., 0.6 MPa, 0.7 MPa, or 0.8 MPa), and the gas charging and discharging time is controlled to be 3-4 min (e.g., 3 min, 3.5 min, or 4 min). Argon is introduced for 3-4 min and then released for 3-4 min.

[0072] Furthermore, the ball milling is performed for 55 to 65 minutes (for example, 55 minutes, 57 minutes, 59 minutes, 61 minutes, 63 minutes or 65 minutes) and then stopped for cooling for 18 to 22 minutes (for example, 18 minutes, 19 minutes, 20 minutes, 21 minutes or 22 minutes).

[0073] Furthermore, the rotation speed of the ball mill is 280-320 r / min.

[0074] In some specific embodiments, the rotation speed of the ball mill can be, for example, but not limited to, 280 r / min, 290 r / min, 300 r / min, 310 r / min or 320 r / min.

[0075] Furthermore, the ball milling time is 4 to 6 hours.

[0076] In some specific embodiments, the ball milling time may be, for example, but not limited to, 4 h, 5 h or 6 h.

[0077] Furthermore, the vacuum drying temperature is 65-75°C.

[0078] In some specific embodiments, the vacuum drying temperature may be, for example, but not limited to, 65°C, 67°C, 69°C, 71°C, 73°C or 75°C.

[0079] Furthermore, the vacuum drying time is 0.8 to 1.2 hours.

[0080] In some specific embodiments, the vacuum drying time may be, for example, but not limited to, 0.8 h, 0.9 h, 1.0 h, 1.1 h or 1.2 h.

[0081] Furthermore, the vacuum degree of the vacuum melting is 4×10 -3 Pa.

[0082] Furthermore, during the vacuum melting, the filling pressure of the inert atmosphere (with a purity higher than 99.99%) is 0.05 MPa.

[0083] Furthermore, the vacuum melting is performed 4 to 6 times.

[0084] Furthermore, the vacuum degree of the single roller belt spinning method is 5×10 -3 Pa.

[0085] Furthermore, the single-roller belt spinning method is carried out under the protection of argon gas (with a purity higher than 99.99%).

[0086] Furthermore, the rotation speed of the cooling roller of the single-roller belt-swinging method is 25 to 35 m / s.

[0087] In some specific embodiments, the rotation speed of the cooling roller of the single-roller belt-spinning method can be, for example, but not limited to, 25 m / s, 27 m / s, 29 m / s, 31 m / s, 33 m / s or 35 m / s.

[0088] The inert atmosphere mentioned in the present invention may be a conventional inert atmosphere in the art, and the specific type is not limited. The inert atmosphere includes but is not limited to argon.

[0089] Another aspect of the present invention also relates to the use of the amorphous foil brazing filler metal for brazing titanium and high nitrogen steel or the preparation method of the amorphous foil brazing filler metal for brazing titanium and high nitrogen steel in brazing titanium and high nitrogen steel.

[0090] Furthermore, the brazing temperature is 1050-1090°C (eg, 1050°C, 1060°C, 1070°C, 1080°C or 1090°C).

[0091] The entire process of the vacuum brazing method of titanium and high nitrogen steel of the present invention is carried out in a vacuum environment. The vacuum environment can prevent the occurrence of hydrogen, oxygen and nitrogen absorption by the base material titanium at high temperature, thereby avoiding the occurrence of defects such as embrittlement, pores, inclusions, etc. caused by absorbing a large amount of gas in the brazing seam area.

[0092] The high nitrogen steel / titanium brazing seam structure obtained by the vacuum brazing method of titanium and high nitrogen steel is mainly composed of α-Ti, Ti(s,s), TiFe and TiFe2, and the room temperature shear strength of the obtained titanium / high nitrogen steel brazing piece is 500-520MPa.

[0093] The titanium involved in the present invention includes: single substance titanium and / or titanium alloy.

[0094] The purity of the raw materials used in the present invention is higher than 99.9%.

[0095] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.

[0096] Example 1

[0097] The amorphous foil brazing material for titanium and high nitrogen steel brazing in this embodiment is composed of the following components in percentage by mass: Fe 10 Ti 90 Alloy 61.2%, Zr 31.2% and Fe 7.6%. The thickness of the titanium-based amorphous foil brazing material is 36μm and the width is 3.5mm.

[0098] The steps of preparing the solder of this embodiment are as follows:

[0099] (1) Weigh Fe with a purity higher than 99% according to mass percentage 10 Ti 90 alloy, Zr single substance with a purity higher than 99.9% and Fe single substance with a purity higher than 99.9% are prepared;

[0100] (2) Place the raw materials weighed in step (1) into a vacuum chamber evacuated to 4 × 10 -3 Pa vacuum arc furnace, then filled with argon gas at a pressure of 0.05 MPa for vacuum melting, melting four times to ensure its uniformity, to obtain Ti-Zr-Fe alloy ingot;

[0101] (3) Take 10g of the alloy ingot cut by wire cutting and put it into a flat quartz glass tube. Put the quartz tube into an induction heating coil and evacuate it to 5×10 -3 After Pa, high-purity argon (purity is 99.99%) is filled in for protection, and after the alloy ingot is completely melted, it is sprayed onto a cooling roller with a rotation speed of 30m / s to prepare an amorphous foil strip solder.

[0102] The Fe used in this example 10 Ti 90 The preparation method is:

[0103] (1) Fe with a purity higher than 99.9% and Ti with a purity higher than 99.9% are weighed and prepared according to the atomic ratio;

[0104] (2) The raw materials weighed in step (1) are sealed together with zirconium oxide grinding balls in a grinding jar of a planetary ball mill, with a ball-to-material ratio of 40:1; the air in the jar is evacuated with a vacuum pump, and 0.8 MPa argon gas (purity of 99.99%) is filled in for protection, and the filling and discharging time of the gas is controlled to be 3 minutes, and the vacuum state is ensured by repeating 3 times;

[0105] (3) Set the ball mill speed to 300 r / min, stop and cool for 20 min after every 60 min of ball milling, for a total of 5 hours. 10 Ti 90 The alloy powder was dried in a vacuum drying oven at 70°C for 1 h and then bagged for later use.

[0106] Example 2

[0107] The amorphous foil brazing material for titanium and high nitrogen steel brazing in this embodiment is composed of the following components in percentage by mass: Fe 20 Ti 80 Alloy 43.5%, Zr 47.2% and Fe 9.3%. The thickness of the titanium-based amorphous foil strip brazing material is 40μm and the width is 4.2mm.

[0108] The method for preparing the solder of this embodiment is the same as that of embodiment 1.

[0109] The Fe used in this example 20 Ti 80 The preparation method is the same as in Example 1.

[0110] Example 3

[0111] The amorphous foil brazing material for titanium and high nitrogen steel brazing in this embodiment is composed of the following components in percentage by mass: Fe 50 Ti 50 Alloy 46.5%, Zr 48.5% and Fe 5%. The thickness of the titanium-based amorphous foil strip brazing material is 40μm and the width is 6mm.

[0112] The steps of preparing the solder of this embodiment are as follows:

[0113] (1) Weigh Fe with a purity higher than 99% according to mass percentage 50 Ti 50 alloy, Zr single substance with a purity higher than 99.9% and Fe single substance with a purity higher than 99.9% are prepared;

[0114] (2) Place the raw materials weighed in step (1) into a vacuum chamber evacuated to 4 × 10 -3 Pa vacuum arc furnace, then filled with argon gas at a pressure of 0.03 MPa for vacuum melting, melting five times to ensure its uniformity, to obtain Ti-Zr-Fe alloy ingot;

[0115] (3) Take 10g of the alloy ingot cut by wire cutting and put it into a flat quartz glass tube. Put the quartz tube into an induction heating coil and evacuate it to 5×10 -3 Pa was then filled with high-purity argon (purity of 99.99%) for protection, and after the alloy ingot was completely melted, it was sprayed onto a cooling roller with a rotation speed of 25 m / s to prepare an amorphous foil strip solder.

[0116] The Fe used in this example 50 Ti 50 The preparation method is:

[0117] (1) Fe with a purity higher than 99.9% and Ti with a purity higher than 99.9% are weighed and prepared according to the atomic ratio;

[0118] (2) The raw materials weighed in step (1) are sealed together with zirconium oxide grinding balls in a grinding jar of a planetary ball mill, with a ball-to-material ratio of 45:1; the air in the jar is evacuated with a vacuum pump, and 0.7 MPa argon gas (purity of 99.99%) is filled in for protection, and the filling and discharging time of the gas is controlled to be 4 minutes, and the process is repeated 3 times to ensure a vacuum state;

[0119] (3) Set the ball mill speed to 280 r / min, stop and cool for 22 min after every 55 min of ball milling, for a total of 6 hours. 50 Ti 50 The alloy powder was dried in a vacuum drying oven at 70°C for 1 h and then bagged for later use.

[0120] Example 4

[0121] The amorphous foil brazing material for titanium and high nitrogen steel brazing in this embodiment is composed of the following components in percentage by mass: Fe 40 Ti 60 Alloy 44.5%, Zr 50% and Fe 5.5%. The thickness of the titanium-based amorphous foil strip brazing material is 45μm and the width is 3mm.

[0122] The steps of preparing the solder of this embodiment are as follows:

[0123] (1) Weigh Fe with a purity higher than 99% according to mass percentage 40 Ti 60 alloy, Zr single substance with a purity higher than 99.9% and Fe single substance with a purity higher than 99.9% are prepared;

[0124] (2) Place the raw materials weighed in step (1) into a vacuum chamber evacuated to 4 × 10 -3 Pa vacuum arc furnace, then filled with argon gas at a pressure of 0.07 MPa for vacuum melting, melting six times to ensure its uniformity, to obtain Ti-Zr-Fe alloy ingot;

[0125] (3) Take 10g of the alloy ingot cut by wire cutting and put it into a flat quartz glass tube. Put the quartz tube into an induction heating coil and evacuate it to 5×10 -3 After Pa, high-purity argon (purity is 99.99%) is filled in for protection, and after the alloy ingot is completely melted, it is sprayed onto a cooling roller with a rotation speed of 35m / s to prepare an amorphous foil strip solder.

[0126] The Fe used in this example 40 Ti 60 The preparation method is:

[0127] (1) Fe with a purity higher than 99.9% and Ti with a purity higher than 99.9% are weighed and prepared according to the atomic ratio;

[0128] (2) The raw materials weighed in step (1) are sealed together with zirconium oxide grinding balls in a grinding jar of a planetary ball mill, with a ball-to-material ratio of 35:1; the air in the jar is evacuated with a vacuum pump, and 0.6 MPa argon gas (purity of 99.99%) is filled in for protection, and the filling and discharging time of the gas is controlled to be 3 minutes, and the process is repeated 3 times to ensure a vacuum state;

[0129] (3) Set the ball mill speed to 320 r / min, stop and cool for 18 min after every 65 min of ball milling, for a total of 4 hours. 40 Ti 60 The alloy powder was dried in a vacuum drying oven at 70°C for 1 h and then bagged for later use.

[0130] Comparative Example 1

[0131] The amorphous foil brazing filler metal for brazing titanium and high nitrogen steel in this comparative example is composed of the following components in percentage by mass: Fe 10 Ti 90 Alloy 70%, Zr 26% and Fe 4%, the preparation method is the same as Example 1.

[0132] Comparative Example 2

[0133] The amorphous foil brazing filler metal for brazing titanium and high nitrogen steel of this comparative example is composed of the following components in mass percentage: 54.2% Ti, 31.2% Zr and 14.6% Fe, and the preparation method is the same as that of Example 1.

[0134] Comparative Example 3

[0135] The amorphous foil brazing filler metal for brazing titanium and high nitrogen steel in this comparative example is composed of the following components in percentage by mass: Fe 60 Ti 40 Alloy 61.2%, Zr 31.2% and Fe 7.6%, the preparation method is the same as Example 1.

[0136] Comparative Example 4

[0137] The amorphous foil solder of this comparative example is composed of the following components in percentage by mass: 33.3% Ti, 16.7% Zr, 39% Cu and 11% Ni. The preparation method is to vacuum melt the single elements and then make the amorphous foil solder by a single-roller strip spinning method.

[0138] Comparative Example 5

[0139] The amorphous foil solder of this comparative example is composed of the following components in percentage by mass: 33.3% Ti, 16.7% Zr, 33.5% Cu and 16.5% Ni. The preparation method is the same as that of comparative example 1.

[0140] Comparative Example 6

[0141] The amorphous foil solder for brazing in this comparative example is composed of the following components in percentage by mass: 37.5% Ti, 37.5% Zr, 10% Ni and 15% Cu. The preparation method is the same as that of comparative example 1.

[0142] Experimental example

[0143] The brazing filler metal provided by the present invention is suitable for brazing connections of all high nitrogen steels and titanium. In the experimental example, only one type of high nitrogen steel and titanium plate are selected to illustrate the effect of the brazing filler metal provided by the present invention. The composition of the high nitrogen steel is as follows according to the weight ratio:

[0144] C; Mn; Cr; Ni; Mo; N; Fe=0.06: 24.5: 22: 2.5: 1.5: 0.75: 48.69.

[0145] The brazing materials prepared in each embodiment and comparative example were subjected to vacuum brazing test, and the vacuum brazing process specifically includes:

[0146] (1) Use wire cutting to process the titanium plate and high nitrogen steel base material into 5×5×5mm 3 and 10×10×5mm 3 The sample to be welded was then polished with 600-grit sandpaper and ultrasonically cleaned in acetone solution for 15 minutes, and finally dried with a hair dryer.

[0147] (2) During brazing, the sample to be welded is assembled using a "sandwich" overlap structure of titanium plate / titanium-based amorphous foil with brazing filler metal / high nitrogen steel, and a graphite block is placed above the assembled sample to provide a vertical pressure of 25 kPa, and the assembled sample to be welded is placed in a brazing furnace;

[0148] (3) Evacuate the vacuum brazing furnace to 5×10 -4Pa, heating was started, and the temperature was increased to 900°C at 10°C / min and kept at that temperature for 10 min. Then, heating was increased to the brazing temperature at 20°C / min and kept at that temperature for 5 min. After cooling in the furnace, the brazing sample was taken out.

[0149] AutoCAD drawing software and mechanical testing machine were used to measure the spreading area of ​​the solder droplets on the surfaces of the two base materials and the bonding strength of the brazed titanium / high nitrogen steel. The bonding strength of the welds obtained at different brazing temperatures was compared and it was found that when the solder of specific embodiment 1 was used for brazing, the optimal brazing temperature was 1070°C, which obtained a good spreading area and excellent mechanical properties. When the brazing temperature was 1070°C, the spreading area on the titanium substrate surface reached a maximum value of 51.9 mm 2 The maximum spreading area of ​​high nitrogen steel surface is 42.7mm 2 The results are shown in Table 1.

[0150] Table 1 Average shear strength of titanium / high nitrogen steel weldments brazed in Example 1 at different temperatures

[0151] Brazing temperature / ℃ Average shear strength / MPa 1050 502.12 1070 519.72 1090 507.88

[0152] Under the condition of a brazing temperature of 1070°C, the brazing filler metals of the embodiment and the comparative example were used, and the titanium plate and the high nitrogen steel were brazed according to the above-mentioned brazing method. The spreading area of ​​the brazing filler metal droplets on the surfaces of the two base materials and the bonding strength of the brazed titanium / high nitrogen steel were tested. The results are shown in Table 2.

[0153] Table 2 Performance test results of different treatments

[0154]

[0155] From Comparative Example 1, it can be seen that using other weight percentages of Ti 10 Fe 90 When alloy, Zr and Fe amorphous solders are brazed, the shear strength and wettability decrease.

[0156] It can be seen from Comparative Example 2 that when brazing is performed using amorphous solder having Ti, Zr and Fe as single-component components in the same weight percentage as in Example 1, both the shear strength and the wettability decrease.

[0157] It can be seen from Comparative Example 3 that the same weight percentage of Ti as in Example 1 is used. 40 Fe 60 When alloy, Zr and Fe amorphous solders are brazed, the shear strength and wettability decrease.

[0158] It can be seen from Comparative Examples 4, 5 and 6 that when other component brazing materials are used for brazing, the shear strength and wettability are both reduced.

[0159] By comparison, it was found that when the brazing filler metal of the embodiment of the present invention was used for brazing titanium / high nitrogen steel heterogeneous joints, the shear strength was higher than that of the control example. The excellent mechanical properties of the titanium-based amorphous brazing filler metal provided by the present invention are helpful to improve the reliability and service life of titanium / high nitrogen steel structural parts in bullet-proof armor protective materials.

[0160] Figure 1 This is a macroscopic picture of the solder of Example 1. Figure 1 It can be seen that the solder has a bright surface, uniform thickness and good toughness, which is conducive to filling gaps and brazing of narrow gap welds.

[0161] Figure 2 is the DSC test curve of the solder of Example 1, Figure 1 It can be determined that the solidus temperature of the solder is 952.97°C, the liquidus temperature is 966.36°C, and the melting temperature range of the solder is 13.39°C. Within this temperature range, the solder presents a semi-solid state, that is, liquid and solid coexist;

[0162] Figure 3 This is the macroscopic morphology of the titanium / high nitrogen steel brazing joint of Example 1. It can be seen that the brazing material is well spread on the high nitrogen steel, and the brazing seam is firmly bonded to form an interface layer. No defects such as unfilled edges and air inclusions are found.

[0163] Figure 4 The EDS surface scan results of the solder of Example 1 are as follows: Figure 4 It can be seen that the amorphous solder has a uniform and dense crystal phase, uniform element distribution, and no segregation. This uniformity determines its narrow melting range, low melting point, and good fluidity and wettability in liquid state.

[0164] Figure 5 The microstructure morphology of the titanium / high nitrogen steel joint brazed by the brazing filler metal in Example 1 is shown in FIG. Figure 5 It can be seen that the weld is mainly composed of three parts, namely the transition zone Zone I close to the high nitrogen steel side, the reaction zone Zone II, and the transition zone Zone III close to the titanium side. According to EDS and XRD analysis, the phases in the weld area are mainly composed of α-Ti, Ti(s,s) and a small amount of TiFe compounds;

[0165] Figure 6 This is the titanium matrix fracture morphology of the titanium / high nitrogen steel joint brazed with the brazing filler metal in Example 1. Figure 6 Obvious cleavage stages can be seen, and the fracture mode is judged to be brittle fracture.

[0166] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.

Claims

1. An amorphous foil brazing material for brazing titanium and high nitrogen steel, characterized in that: According to weight parts, it includes the following components: Fe x Ti (100-x) Alloy 35-65 parts, Zr 30-50 parts and Fe 5-10 parts; Among them, the value of x is 10~50.

2. The amorphous foil brazing filler metal for brazing titanium and high nitrogen steel according to claim 1, characterized in that: According to weight parts, it includes the following components: Fe x Ti (100-x) Alloy 43.5-61.2 parts, Zr 31.2-47.2 parts and Fe 7.6-9.3 parts; Among them, the value of x is 10~50.

3. The amorphous foil brazing filler metal for brazing titanium and high nitrogen steel according to claim 1 or 2, characterized in that: The width of the amorphous foil brazing material for brazing titanium and high nitrogen steel is 3 to 6 mm; And / or, the thickness of the amorphous foil brazing material for brazing titanium and high nitrogen steel is 35-45 μm.

4. The amorphous foil brazing filler metal for brazing titanium and high nitrogen steel according to claim 1 or 2, characterized in that: The melting point of the amorphous foil brazing material for brazing titanium and high nitrogen steel is 930-1030°C.

5. The method for preparing amorphous foil brazing filler metal for brazing titanium and high nitrogen steel according to any one of claims 1 to 4, characterized in that: The following steps are involved: (a) vacuum melting the raw materials under an inert atmosphere to obtain an alloy ingot; (b) The alloy ingot is subjected to amorphous forming treatment by a single-roll strip spinning method.

6. The method for preparing amorphous foil brazing filler metal for brazing titanium and high nitrogen steel according to claim 5, characterized in that: The Fe x Ti (100-x) The preparation method of the alloy includes: The iron element and the titanium element are mixed, ball-milled and vacuum-dried.

7. The method for preparing amorphous foil brazing filler metal for brazing titanium and high nitrogen steel according to claim 6, characterized in that: The ball-to-material ratio of the ball mill is 35-45:

1.

8. The method for preparing amorphous foil brazing filler metal for brazing titanium and high nitrogen steel according to claim 6, characterized in that: The ball milling is carried out under the protection of an inert gas, the filling pressure of the inert atmosphere is 0.6-0.8 MPa, and the filling and discharging time of the gas is controlled to be 3-4 minutes.

9. The method for preparing amorphous foil brazing filler metal for brazing titanium and high nitrogen steel according to claim 6, characterized in that: The invention comprises at least one of the following technical features (1) to (3): (1) The rotation speed of the ball mill is 280-320 r / min; (2) The ball milling time is 4 to 6 hours; (3) The ball milling is stopped and cooled for 18 to 22 minutes every 55 to 65 minutes.

10. Use of the amorphous foil brazing filler metal for brazing titanium and high nitrogen steel as claimed in any one of claims 1 to 3 or the amorphous foil brazing filler metal for brazing titanium and high nitrogen steel as claimed in any one of claims 4 to 9 in brazing titanium and high nitrogen steel.

Citation Information

Patent Citations

  • Laser-electric arc two-heat source weak coupling welding method for high-nitrogen steel

    CN111515542A

  • Flux-cored wire for laser-arc hybrid welding of high-nitrogen steel

    CN115464301A